Rapid and controllable a-Si:H-to-nc-Si:H transition induced by a high-density plasma route. (29th August 2017) - Zhou, H P; Xu, M; Xu, S; Xu, L X; Ji, H; Xiao, S Q; Feng, Y Y
Abstract: The low-temperature rapid solid phase crystallization route of amorphous silicon is fundamentally and technologically significant. Micrometer thick hydrogenated amorphous silicon (a-Si:H) films were exposed to a low-frequency inductively coupled hydrogen plasma under a low substrate temperature of 300 °C. The plasma treated a-Si:H was completely crystallized within half an hour. The evolution of microstructures, optical and electric properties with respect to plasma exposure duration deterministically demonstrates that the present low-temperature rapid crystallization process enables the controllable phase transition from amorphous to nanocrystalline (nc) silicon. The crystallization mechanism is discussed in terms of the unique characteristics of low-frequency inductively coupled plasma (LFICP) and the LFICP-grown precursor a-Si:H film itself. The crucial role of hydrogen atoms in the phase transition is also discussed.